BATHYMETRIC SURVEY USING MULTIBEAM ECHOSOUNDER IN SETANGGA WATERS, TANAH BUMBU REGENCY, SOUTH KALIMANTAN PROVINCE - Ramadhani, Suci; Ismail, R. Moh; Wardono, Suko (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
Bathymetry studies the depth and topographic features of the seabed, which aremapped using underwater acoustic technologies such as Multibeam Echosounder. This research was conducted in the Setangga Waters, Tanah Bumbu Regency, South Kalimantan Province, using a Multibeam Echosounder T-20P. Data acquired from a four-day survey were processed using PDS software, including data cleaning, Sound Velocity Profile (SVP) correction, and tidal correction. Tidal data were processed using LP-TIDES software based on 26 days of observations, resulting in a Mean Sea Level (MSL) value of 1.08 meters. All data met the International Hydrographic Organization (IHO) standards, and the final results were presented in the form of a Digital Elevation Model (DEM) and depth contour maps that accurately represent the seabed morphology.